2013
DOI: 10.14206/canad.j.clin.nutr.2013.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Practice and Physical Activity in Children with Down Syndrome and Their Siblings in Saudi Arabia

Abstract: Background: Feeding difficulties and inappropriate nutrition are common problems among children with Down Syndrome (DS). Objective: The aim of this study is to investigate the dietary practice and physical activity among children with DS. Methodology: The study groups were pre-pubertal DS boys and girls, aged 5 to 12 years clinically and cytogenetically proven to be suffering from DS. Healthy siblings, closest in age to the DS children were used as a control group. Breast feeding, eating difficulties, fast foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…This result is in agreement with the studies done by Mohamed et al (2013) and Mitchell et al (2003) who found feeding difficulties in CWDS. Hennequin et al (2000) also found that suckling, swallowing and chewing were delayed, and the feeding pattern was found to be an intermediate pattern between a primary suckle-swallow pattern and full rotary chewing.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This result is in agreement with the studies done by Mohamed et al (2013) and Mitchell et al (2003) who found feeding difficulties in CWDS. Hennequin et al (2000) also found that suckling, swallowing and chewing were delayed, and the feeding pattern was found to be an intermediate pattern between a primary suckle-swallow pattern and full rotary chewing.…”
Section: Discussionsupporting
confidence: 93%
“…The results indicated that the children with Down syndrome faced greater difficulties in solids than liquids in both the phases of the swallow. The present study is in consensus with the study conducted by Mohamed et al (2013) who found difficulties in the transition from liquids to solids in CWDS. Gisel et al (1984) revealed that CWDS exhibited a reluctance to chew and preferred sucking of food with decreased masticatory efficiency when it comes to chewing solids.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations